Оценка комплексной терапии, включающей Фемибион 2, в профилактике и коррекции первичной плацентарной недостаточности - Е. Н. Маланина; Л. Ю. Давидян; Д. Р. Касымова (Архивъ внутренней медицины, 2011)
Prevention and treatment of primary placental insufficiency is a condition for the preservation and normal duration of pregnancy. An assessment of pregnancy in 197 women with primary placental failure, 89 of whom received progesterone analog and Femibion, was provided. Recommendations for the evaluation of gestation were estimated, the data, allowing usage the specified treatment for the correction of gestational complications, were determined.